2010
DOI: 10.1021/jp105186z
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Process Determines Ultrafast Excited State Deactivation of Thioflavin T in Low-Viscosity Solvents

Abstract: Here we provide first direct experimental results about photoinduced TICT-state formation for Thioflavin T (ThT). In this work, femtosecond transient absorption spectra dynamics for ThT, dissolved in low-viscosity solvents (water, ethanol, 2-propanol, butanol) was investigated. It was found that decay lifetime of fluorescent LE-state for ThT in low-viscous solvents does not exceed 12 ps, and its value correlates well with rising time of the absorption band at 470 nm. It indicates that LE-state of ThT initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
142
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 44 publications
16
142
1
5
Order By: Relevance
“…Stsiapura et al reported the time evolution of the TA spectrum in the l = 520-600 nm region, which could reveal the evolution of the ESA band only, but missed the SE band in the l = 700-950 nm region, which is an important feature of the relaxed excited state of ThT. [33] This SE band has been observed for the first time in this work.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…Stsiapura et al reported the time evolution of the TA spectrum in the l = 520-600 nm region, which could reveal the evolution of the ESA band only, but missed the SE band in the l = 700-950 nm region, which is an important feature of the relaxed excited state of ThT. [33] This SE band has been observed for the first time in this work.…”
Section: Resultssupporting
confidence: 48%
“…Earlier, Stsiapura et al also reported that bleach recovery was not complete in the 20 ps time domain. [33] They attributed the incomplete recovery of the ground state of ThT to the photochemical ring opening of the benzothiazole moiety of the molecule. However, the proposition of the photochemical reaction possibly can be ruled out on the basis of the fact that ring opening of ThT would lead to a loss of conjugation, and thus, absorption spectra of the resulting molecular fragments would appear only in the UV region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) -Um anel Benzotiazol Os três grupos que formam a estrutura da Tioflavina T são muito rígidos e tanto a sua estrutura quanto o comportamento fotofísico são determinados majoritariamente pelas suas orientações espaciais [88,89].…”
Section: Tioflavina Tunclassified
“…Estudos recentes demonstraram que a ThT comporta-se com um Rotor Molecular [88], [89], [90]. Rotores moleculares são moléculas fluorescentes caracterizados pela capacidade de formar estados torcidos através da rotação de um dos seus fragmentos com relação ao restante da molécula [91].…”
Section: Tioflavina Tunclassified